The times they are a-changing: who will stay and who will go in a downsizing organization? - Cross, B.; Travaglione, Tony (MCB University Press, 2004)
The recent growth in the trust literature indicates that both researchers and practitioners are continuing to recognise its importance as a factor for determining organisational success and the well‐being of employees. Trust is, however, a complex, multidimensional construct that has generated much debate concerning how trusting relationships might be created. The aim of this paper is to add to current debates by reporting on a study concerning trust within manager‐subordinate relationships within a large Australian organisation. The annual staff survey for this organisation indicated that levels of trust in managers were very low, leading the authors to investigate the predictors and outcomes of this situation. Focus group and survey questionnaire results led to the finding that perceived organisational support, procedural justice and transformational leadership were significant predictors of trust in managers and that turnover intent and commitment were significant outcomes. The implications of these findings for researchers and practitioners are discussed.